PANDANGAN MAQASID SYARIAH DALAM PENGELOLAAN DANA HAJI MELALUI SUKUK - Gina Maulida Ndraha; Marliyah Marliyah; Muhammad Arif (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
From the results of the analysis of this study it was found that the Hajj funds managed by the Ministry of Finance were combined with funds from debt financing sources which then entered into the state treasury which was allocated to debt financing in the budget financing section which functioned to cover short-term cash shortages where cash differences appeared when the available state treasury is unable to suffice for expenditures that cannot be postponed. The effectiveness of the management of the Hajj funds can be seen from the improvement in the quality of organizing the Hajj (lodging, catering and transportation) and the Cost of Organizing the Hajj (BPIH). With BPIH in 2018 of Rp. 31 million pilgrims have received the best facilities with 3 star accommodation, safe and secure transportation and timely catering, clean and healthy food is also delivered according to time and portion. This is proof that the management of haj funds at SDHI is effective because the results of these yields can cover half of the service needs and costs of Indonesian haj.